PROGRAM PENGELOLAAN BUMDes TAHUN 2020-2021 STUDI: BUMG GAMPONG TUMPOK TEUNGOH KOTA LHOKSEUMAWE - Baihaqi, M; Rasyidin, Rasyidin; Nirzalin, Nirzalin (Jurnal Transparansi Publik (JTP), 2022)
The rule or regulation of the Minister of PDTT No. 4 of 2015, which describes the management, formation, and dissolution of BUMD, goes into more depth about the implementation of village community empowerment. We may comprehend that BUMG is financed by villages, with village money used to carry out village capital participation. BUMG offers services aimed at boosting local businesses and economies in order to build a flourishing community welfare state. In order to provide a comprehensive and in-depth picture of the implementation of Lhokseumawe Mayor Regulation Number 31 of 2017 at BUMG Gampong Tumpok Teungoh, Lhokseumawe City in 2020-2021, a descriptive qualitative research methodology was utilized. The findings of the study and conversation on BUMG's contribution to community improvement. The findings of the research and discussion on BUMG's role in enhancing the community's economy have been realized, but they have not been successful, particularly in the implementation of BUMG reporting and the development of existing potential so that the economy of the Gampong community can improve social welfare, BUMG also contributes as a substitute for The Original Income. Gampong (PAG) remains incredibly low. Gampong Bumg To increase the efficiency of business units and the efficiency of its management's human resources, Gampong Tumpok Teungoh management should focus more on and enhance institutional management and BUMG reporting. The role of Gampong-Owned Enterprises in Developing Business and Community Economy is projected to be the subject of future investigation, which is anticipated to be more thorough and comprehensive